S22 The liverpool healthy lung project – raising the importance of lung health. (12th November 2019) - Ledson, MJ; Ahmed, M; Arvanitis, R; Timoney, M; Gaynor, E; Field, J
Abstract : Liverpool has high levels of deprivation and one of the highest rates of respiratory morbidity in England with double the incidence of lung cancer, most prevalent in the lower socioeconomic groups. To tackle this health inequality, in February 2016 in partnership with Liverpool CCG, Liverpool University, and primary care and public health colleagues, we embarked on the 4-year Liverpool Healthy Lung Project. Based on primary care records, individuals aged 58–75 with COPD, a history of smoking or asbestos exposure were invited to a face-to-face lung health check conducted by an experienced respiratory nurse. At this interview positive lifestyle messages were promoted and their 5-year personal lung cancer risk calculated (www.MyLungRisk.org) using the LLPv2 risk model. Those without a diagnosis of COPD underwent spirometry, and those who triggered the 5% threshold lung cancer risk threshold were offered a low dose thoracic CT scan. We now report our results to April 2019, when 11436 of 28590 (40%) patients invited to the lung health check had attended. Of these, 6632 (58%) underwent spirometry and 10% were diagnosed with COPD. A further 3812 (34%) underwent the CT scan and of these 126 (3.3%) were suspicious of malignancy. Lung cancer was ultimately diagnosed in 76 (2%) and 61 of these (80%) were offered radical treatment. Of the remaining 50 patients, 11 underwent an invasive test and there was 1 benign resection. 343 patients (9%) needed repeat scans for lung nodules. These early results show that this innovative project is already improving access to respiratory healthcare in a deprived area of Liverpool, has identified new COPD patients, and over time should improve outcomes for lung cancer in this disadvantaged population.